Nitrogen removal via nitrite in a partial nitrification sequencing batch biofilm reactor treating high strength ammonia wastewater and its greenhouse gas emission. (April 2017) - Wei, Dong; Zhang, Keyi; Ngo, Huu Hao; Guo, Wenshan; Wang, Siyu; Li, Jibin; Han, Fei; Du, Bin; Wei, Qin
Graphical abstract: Highlights: Partial nitrification was successfully achieved and maintained in a SBBR. PN and PS contents were reduced during the achievement of PN process. 3D-EEM implied that LB-EPS and TB-EPS had similar chemical compositions. CO2 and N2 O emission amounts per cycle were 67.7 mg and 16.5 mg. Abstract: In present study, the feasibility of partial nitrification (PN) process achievement and its greenhouse gas emission were evaluated in a sequencing batch biofilm reactor (SBBR). After 90 days' operation, the average effluent NH4 + -N removal efficiency and nitrite accumulation rate of PN-SBBR were high of 98.2% and 87.6%, respectively. Both polysaccharide and protein contents were reduced in loosely bound extracellular polymeric substances (LB-EPS) and tightly bound EPS (TB-EPS) during the achievement of PN-biofilm. Excitation-emission matrix spectra implied that aromatic protein-like, tryptophan protein-like and humic acid-like substances were the main compositions of both kinds of EPS in seed sludge and PN-biofilm. According to typical cycle, the emission rate of CO2 had a much higher value than that of N2 O, and their total amounts per cycle were 67.7 and 16.5 mg, respectively. Free ammonia (FA) played a significant role on the inhibition activity of nitrite-oxidizing bacteria and the occurrence of nitrite accumulation.